A metric approach to measure resilience in water supply systems. Issue 1 (2nd January 2019) - Cubillo, Francisco; Martínez-Codina, Ángela
Abstract : Water utilities face challenges and should ensure overall resilience. A comprehensive calculation of resilience for unusual problems and frequent events is proposed. The resilience definition includes the capacity of a system to delimit impacts in the aftermath of a disruptive event. Different types of threats are classified in consideration of water service disruption: (A) water scarcity, (B) water supply discontinuity, (C) discontinuity of hydraulic conditions and (D) discontinuity of drinking water quality conditions. Failure thresholds distinguish: (1) a standard level, (2) a normative level, (3) an accepted level and (4) a critical level. The resilience model considers service level and time and is modified by protocols, resources and technologies. The methodology is applied to the water supply system managed by Canal de Isabel II (Spain). The case studies are a drought, pipe breaks and water quality failures. Real data help managers contrast the effectiveness of their protocols and plan investments.